2022
DOI: 10.1007/s12063-022-00343-y
|View full text |Cite
|
Sign up to set email alerts
|

How blockchain technology improves sustainable supply chain processes: a practical guide

Abstract: Blockchain technology has rapidly grown in the last decade and supply chain management has started to emerge as one of its possible fields of application. Blockchain is estimated to have a transformative impact and potentially transform and disrupt supply chains. However, despite recognizing its enormous opportunity, there is still an incomplete, dispersed, and fragmented knowledge of blockchain applications beyond cryptocurrencies. Very few business people still deeply understand how blockchain works and how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Difrancesco et al [156] claim that blockchain improves supply networks that are sustainable. It was concluded that sourcing and manufacturing, inventory management, distribution and delivery, retail, customer experience, product returns, and reverse logistics are the six main supply chain activities for blockchain applications.…”
Section: Ii) Analysis Of Factors For Adoption Of Blockchain Technolog...mentioning
confidence: 99%
See 1 more Smart Citation
“…Difrancesco et al [156] claim that blockchain improves supply networks that are sustainable. It was concluded that sourcing and manufacturing, inventory management, distribution and delivery, retail, customer experience, product returns, and reverse logistics are the six main supply chain activities for blockchain applications.…”
Section: Ii) Analysis Of Factors For Adoption Of Blockchain Technolog...mentioning
confidence: 99%
“…[29], [59], [83], [141], [156] Discussions 7 [2], [5], [60], [80], [95], [104], [119] Bibliometric analysis 3 [46], [85], [94],…”
mentioning
confidence: 99%
“…By applying blockchain technology to supply chain management, companies can offer unequivocal proof of sustainable practices, from sourcing raw materials to delivering the final product (12). This transparency encourages ethical sourcing and production methods, driving the adoption of more sustainable business practices.…”
Section: Streamlining Supply Chain Management For Sustainable Practicesmentioning
confidence: 99%
“…In supply chain management, for example, blockchain can be used to create a permanent and transparent record of the journey of goods from manufacture to sale, reducing the likelihood of fraud and errors [ 64 ]. The technology's aptitude for automating transactions, eliminating intermediaries, and thus streamlining operations, makes it particularly beneficial for several applications beyond finance, including supply chain management, healthcare, and even voting systems [ [65] , [66] , [67] ].…”
Section: Introductionmentioning
confidence: 99%